DEVELOPMENT OF INFORMATION COMPETENCE OF FUTURE MATHEMATICS TEACHERS BY MEANS OF COMPUTER VISUALIZATION - Horoshko , Oleksandr (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The need for high-quality training of future mathematics teachers, the rapid development of communication and computer technologies, the increase in the amount of information require new approaches to education. The article is devoted to the problem of developing information competence of future mathematics teachers and the role of computer visualization in this process.